A Pannoniakutató Járdányi-Paulovics István (1892–1952) - Gesztelyi, Tamás (Gerundium, 2016)
István Járdányi-Paulovics (1892–1952), Researcher of Pannonia. István Járdányi-Paulovics’s professional interest first turned to the study of the remains of Egyptian cults in Pannonia. His excavation work began in Intercisa, later he continued this activity in Brigetio and Savaria. In all three cases he produced memorable results despite the fact that subsequent excavations often failed to confirm his assumptions. In the case of Brigetio, he produced publications of enduring merit on the small bronze age and the analysis of the inscriptions of a law tablet. The most vivid interest was generated by the exploration of the excavations in the so-called Quirinus basilica in Savaria, which in the meantime has come to be regarded by more recent research as the palace of the procurator. His definition pertaining to the Capitolean Trias has been equally controversial. Between 1940 and 1952, at the University of Debrecen he invigourated the study of ancient history and of provincial archaeology.